Electrochemical Pinacol Coupling of Acetophenone Using Boron‐Doped Diamond Electrode. Issue 16 (21st March 2019) - Nakahara, Kenshin; Naba, Keisuke; Saitoh, Tsuyoshi; Sugai, Tomoya; Obata, Rika; Nishiyama, Shigeru; Einaga, Yasuaki; Yamamoto, Takashi
Abstract: An electrochemical pinacol coupling reaction of acetophenone using a boron‐doped diamond (BDD) electrode has been reported. This transformation is driven by the one‐electron reduction of acetophenone on the BDD cathode, followed by an intermolecular radical coupling. Owing to the BDD's outstanding electrochemical properties, the pinacol‐type compound has been obtained in good conversion yield. The roles of a supporting electrolyte and solvent were addressed; (1) lithium ions contribute to increase in the reactivity of the radical intermediate. (2) Addition of water promotes the electron transfer process at the BDD surface. The reaction is relatively tolerant to para ‐substituted acetophenone derivatives. Since electric current is directly employed as reducing reagents to generate a radical intermediate, the reaction is metal‐free, sustainable, and inherently safe. Abstract : Farewell to metals : boron‐doped diamond (BDD) is a carbon‐based, highly robust electrode material for electrosynthesis. The BDD cathode enables metal‐free pinacol coupling reactions of acetophenone. The presented protocol is sustainable and inherently safe, which provides new perspectives for the old pinacol coupling reaction.